Dinamika Penentuan Awal Ramadan di Sumatera Barat - Urwatul Wusqa; Salma Salma; Walan Yudhiani (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
This paper aims to explore the understanding of the Muslim community of West Sumatra about the determination of the beginning of the month of Ramadan and its implications for implementing the first day of fasting. The people of West Sumatra are always talked about when determining the first day of Ramadan because they are divided into several groups. As a result, they differ in the implementation of the first day of fasting, the implementation of Eid al-Fitr and Eid al-Adha. This type of research is field research. Data obtained through in-depth interviews with people who can provide important information about the determination of the beginning of this month, including the leader of Naqsabandiyah, Satariyah, person in charge of hisab Muhammadiyah, ru'yah NU, astronomy experts, as well as several congregations from each group. The results showed that determining the start of the month is a very old problem but always becomes new every time Ramadan comes. The problem of determining the initial crescent moon in Indonesia in general and West Sumatra in particular is basically the same but the practice depends on the different ways of understanding the context of the initial crescent of the month. In fact, these differences are very difficult to reconcile because each element remains steadfast in maintaining its sectoral ego.